Epidemiological aspects of facial trauma in a third level hospital in Mexico - Mejía Rivera, Samaria E.; Olivares, Eduardo P.; Del Pino, Paulina S.; Monroy, Ricardo C.; Piña, Raymundo T.; Martinez, Grecia C. M.; Campos, Alan M. H. (International Journal of Research in Medical Sciences, 2023)
Background: Facial trauma is common in early adulthood and may require complex surgery and even high mortality. Methods: Retrospective, cross-sectional study at the Hospital General de México during the period from January 2018 to December 2021. Patients with a diagnosis of fracture of the facial region, who had a complete clinical record, of any age, were included. Patients who did not comply with the treatment in the hospital unit, with incomplete clinical records, were excluded. Through non-probability sampling, a sample of 156 patients was formed. The descriptive data analysis was carried out by calculating frequencies and percentages for the qualitative variables. For the quantitative variables, measures of central tendency and dispersion were calculated according to the distribution of the variables (mean and standard deviation). for variables with normal distribution and median with interquartile range for variables with non-normal distribution). Results: 156 patients were included, the male sex predominated (89.7%), the age group from 21 to 30 years (35.3%), the injury mechanism of aggression by a third party (54.5%). Facial fractures occurred in the following descending order: orbit (64.7%), zygoma (41.7% n=65), mandibular (23.1% n=36), nasal (22.4% n=35), maxilla (21.8% n=34), NOE (4.5% n=7), Le Fort (3.8% n=6), and palate (3.8% n=6). Within orbital fractures, the most frequently affected region was the orbital floor (42.3%). The patients with orbital fracture were mostly men (88.1% versus 11.9%). The highest frequency of these fractures was between the ages of 21 and 30 (38.6%). Surgical treatment of fractures in general was established in 44.9%, performing open reduction and internal fixation of fractures in 41.0%. Conclusions: The most frequent facial fractures are: orbit, zygoma, and mandibular; they mainly affect the male sex in the second decade of life, they are produced mainly by aggressions to third parties. The management of facial fractures is predominantly surgical, through open reduction and internal fixation.